Enhancing Medication Safety: The Role Of Pharmacology Technicians In Error Prevention And Risk Management (The Review of Diabetic Studies, 2025)
Medication errors pose a significant global health challenge, contributing to preventable harm, increased morbidity and mortality, and substantial financial burdens on healthcare systems. Pharmacology technicians play a crucial role in mitigating these risks through their involvement in various stages of the medication use process. This review elucidates the vital contributions of pharmacology technicians in preventing medication errors and managing risks within the healthcare safety paradigm. By examining the conceptual framework of medication safety, the evolving roles and responsibilities of technicians, and the types and causes of errors, this review highlights the importance of technician-led interventions. Pharmacology technicians enhance safety through prescription verification, ensuring dispensing accuracy, and supporting pharmacovigilance efforts. The integration of technology, including automation, electronic prescribing, barcode medication administration, and artificial intelligence, further empowers technicians to intercept errors and optimize medication use. Effective risk management strategies, such as failure mode and effects analysis, root cause analysis, and promoting a blame-free reporting culture, are essential for continuous quality improvement. Emphasizing the significance of education, training, and competency development, this review underscores the need for structured programs and interprofessional collaboration to prepare technicians for their expanding roles. Recent evidence from global studies, comparative analyses, and systematic reviews demonstrates the positive impact of technician interventions on reducing medication errors across various healthcare settings. Future perspectives highlight the potential for technicians to contribute to precision medicine, telepharmacy, and the integration of artificial intelligence in decision support systems. Ultimately, policy reforms aimed at standardizing technician practice globally are necessary to harness their full potential in promoting medication safety and optimizing patient outcomes.